Successful experience with implantation of a pilot project of a Living Pharmacy in Araraquara-SP - Moreira, Raquel Regina Duarte [UNESP]; do Nascimento Baldo, Matheus [UNESP]; Pierri, Maria Eduarda Senna [UNESP]; Geanfrancesco, Caio [UNESP]; Leite, Ana Luiza Mamede [UNESP]; de Oliveira, José Ricardo Soares; da Silva, Érica Tomé; Fagnani, Luciano Roberto; Bertolini, Erick Vinicius; da Silva, Silvani; Guerrero, Ana Maria Quílez (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
The Living Pharmacy (FV) Program was planned with the aim of producing quality herbal medicines with guaranteed safety and efficacy from validated medicinal plants, seeking to offer a therapeutic option, in addition to developing educational work on the correct use of medicinal plants. This article aims to describe the implementation of a FV pilot project at the Family Health Unit (USF) in Araraquara, with the aim of offering phytotherapy as a therapeutic resource, promoting the rational use of medicinal plants in Primary Health Care (PHC), rescuing popular knowledge based on scientific knowledge. A survey of the main diseases that affect the local population was carried out and, from there, the medicinal plants of the project were selected. Subsequently, the preparation of the land for the cultivation of seedlings began. Concomitantly, conversation circles, courses and workshops were held with the community and the USF health team on the preparation of seedlings and the rational use of medicinal plants. The results showed that anxiety, respiratory and gastric problems, and inflammation are the conditions that most affect the local population. The following species were selected to be cultivated: Curcuma longa (turmeric), Cymbopogon citratus (lemon grass), Lippia alba (lippia), Maytenus ilicifolia (espinheira santa), Mikania glomerata (guaco) and Plectrantus barbatus (boldo nacional), following the Phytotherapic Formulary of the Brazilian Pharmacopoeia. The conversation circles, workshops and courses made it possible for the community and local health team to access scientific information, in simple language, valuing exchanges of experiences, describing medicinal plants, their therapeutic properties, preparation, dosage and contraindications. The tea workshops allowed participants to rescue the family’s affective memory, an important factor for the success of the FV project. The FV is a social project that has demonstrated to rescue the community’s self-esteem and the ability to guide the rational use of medicinal plants, valuing phytotherapy as a therapeutic resource of choice in the health system.
Experiência exitosa na implantação de projeto piloto de Farmácia Viva em Araraquara-SP
Keywords: Health education; Herbal medicine; Medicinal plants; Primary health care